Analisis pengaruh pelayanan IGD terhadap kepuasan pasien di rumah sakit Omni Cikarang tahun 2021 - Safuranti, Aristya Maulida; Fitriani, Arifah Devi; Nasution, Ramadhani Syafitri (Journal of Pharmaceutical and Sciences, 2024)
Background: The Emergency Room (IGD) is one of the service units in hospitals that provides first aid. Emergency services provided must meet good service quality. Patients are satisfied with the services of nurses in the ER if the patient's expectations are met. According to WHO, health systems should strive to make improvements in six areas or dimensions of quality. Objectives: To analyze the effect of emergency services on patient satisfaction at OMNI Cikarang Hospital in 2021. Method: This type of research is an analytical survey method with a cross sectional approach. The research was carried out at OMNI Cikarang General Hospital. The population of this study were emergency room patients with the number of samples in this study as many as 92 people through the calculation of the slovin formula. Sampling using accidental sampling technique. Data analysis used univariate, bivariate and multivariate analysis. Results: Showed that the respondents who were satisfied were 40 people (43.5%) and 52 people (56.5%) were not satisfied with the emergency room service. The results of the chi-square statistical test showed that the variables of effectiveness, efficient, accessible, acceptable, impartial and safe had an influence on patient satisfaction with a p value of <0.05. Simultaneous test results showed that the effectiveness factor was the most dominant factor influencing patient satisfaction in the OMNI Cikarang Emergency Room. Conclusion: There is an effect of effectiveness, efficiency, access, acceptable, impartial and safe has an effect on patient satisfaction in the ER OMNI Cikarang. It is recommended to health workers to always improve better services in order to increase patient satisfaction as users of health services.